Managing resources for sustainable agriculture in South Asia - Gill, Gerard J. (International Food Policy Research Institute, 1996)
In the next 25 years, South Asia's food requirements are likely to double, while its natural resource base is likely to shrink. The subcontinent, which carries 21 percent of the world's population on just 3 percent of its land area, already has a high proportion of its land under cultivation and relatively little under forest and pastures (Figure 1). Industrialization and urbanization will further encroach on agricultural and forest land. Over the next quarter century, countries in the region will need to feed their growing populations on increasingly restricted natural resources, with the added requirement of safeguarding the environment and natural resource base. The author describes the current state of the natural resource base and explores ways of managing resources in unfavored areas and in favored areas.